2017
DOI: 10.1099/jgv.0.000851
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of antibodies to core+1/ARF protein in HCV-infected patients with advanced cirrhosis

Abstract: Hepatitis C virus (HCV) possesses a second open reading frame (ORF) within the core gene encoding an additional protein, known as the alternative reading frame protein (ARFP), F or core+1. The biological significance of the core+1/ARF protein remains elusive. However, several independent studies have shown the presence of core+1/ARFP antibodies in chronically HCV-infected patients. Furthermore, a higher prevalence of core+1/ARFP antibodies was detected in patients with HCV-associated hepatocellular carcinoma (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 42 publications
0
13
0
6
Order By: Relevance
“…During acute HCV infection, seroconversion to anti-core+1 antibodies can be observed [238]. Patients with chronic HCV infection, liver cirrhosis, and hepatocellular carcinoma have many more antibodies against core+1 products than other patients, and the antibody titers correlate with the extent of liver cirrhosis [239][240][241]. These findings show that ARF/core+1 actually is expressed in chronic HCV infection of the liver, and the extent of ARF/core+1 expression (likely as overall HCV expression) in the liver correlates with the extent of liver damage.…”
Section: Expression Of the Alternative Reading Frame Arf/core+1mentioning
confidence: 99%
“…During acute HCV infection, seroconversion to anti-core+1 antibodies can be observed [238]. Patients with chronic HCV infection, liver cirrhosis, and hepatocellular carcinoma have many more antibodies against core+1 products than other patients, and the antibody titers correlate with the extent of liver cirrhosis [239][240][241]. These findings show that ARF/core+1 actually is expressed in chronic HCV infection of the liver, and the extent of ARF/core+1 expression (likely as overall HCV expression) in the liver correlates with the extent of liver damage.…”
Section: Expression Of the Alternative Reading Frame Arf/core+1mentioning
confidence: 99%
“…Consecutive blood samples were obtained from the patients at the time point of before, during (12,24, and 48 weeks), and 6 months after ETR. Responders were defined as patients with no detectable HCV RNA at the ETR and at least 6 months after ETR, while non-responders were defined as patients unclear for HCV RNA at the ETR.…”
Section: Resultsmentioning
confidence: 99%
“…The detection of high levels of specific anti-core+1 antibodies in patients infected with HCV and HCC provides strong evidence that core+1 is produced during natural infection and may have a role in the progress to advanced stages of HCV liver disease (1,12,19,20). In the study by Park et al (21), it was shown that the expression of core+1 can lead to suppression of types I and III interferon (IFN) responses in hepatocytes, suggesting the important role of the core+1 in the modulation of host innate immunity by HCV.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations